2010
DOI: 10.1021/om100183a
|View full text |Cite
|
Sign up to set email alerts
|

Osmium Complexes Containing N-Heterocyclic Carbene-Based C,N,C-Pincer Ligands

Abstract: Osmium(II) complexes bearing C,N,C-pincer ligand 2,6-bis(alkylimidazolin-2-ylidene)pyridine (CNC-Me and CNC-Bu for alkyl = methyl and n-butyl, respectively) or 2,6-bis(3-butylbenzimidazolin-2-ylidene)pyridine (CNC 0 -Bu) and aromatic diimine (2,2 0 -bipyridine (bpy)/1,10-phenanthroline (phen)) have been prepared. The X-ray crystal structure of [Os(CNC-Me)(bpy)Cl](PF 6 ) shows that the Os-C bonds are essentially single (Os-C distances = 2.042(4) and 2.059(4) A ˚). Spectroscopic comparisons of [Os(C,N,C)(diimine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…These complexes show their enhanced catalytic activity in many organic reactions especially in CeC coupling reactions [16,20,25,28]. Pincer complexes of transition metals such as iridium [31], rhodium [32], ruthenium [33,34], and osmium [35] have found applications in olefin metathesis, hydrogen transfer, hydrosilylation, hydroformylation and polymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes show their enhanced catalytic activity in many organic reactions especially in CeC coupling reactions [16,20,25,28]. Pincer complexes of transition metals such as iridium [31], rhodium [32], ruthenium [33,34], and osmium [35] have found applications in olefin metathesis, hydrogen transfer, hydrosilylation, hydroformylation and polymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1‐Bu, 2‐Bu, and 3‐Bu showed similar weak absorption bands at λ = 500–800 nm due to the C,N,C‐pincer ligands. 1‐Bu and 2‐Bu derivatives are less conjugated than the 3‐Bu derivative, but these have higher energy than the π*(tpy) [25]…”
Section: Thiocyanate‐free Osmium Sensitizer For Solar Cellsmentioning
confidence: 99%
“…Amino and imino functionalized NHC palladacycles have displayed remarkably enantiomeric excess values of up to 92% in asymmetric allylic alkylation reaction . Pyridine‐functionalized NHCs have also attracted recent interest and have demonstrated good potential in different catalytic scenarios . Crabtree et al and Hahn et al have previously reported a series of palladium tridentate NHC complexes and successfully applied them to the catalysis of the Heck reaction.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Pyridine-functionalized NHCs have also attracted recent interest and have demonstrated good potential in different catalytic scenarios. [34][35][36][37][38][39][40][41][42][43][44][45][46] Crabtree et al 47,48 and Hahn et al 49 have previously reported a series of palladium tridentate NHC complexes and successfully applied them to the catalysis of the Heck reaction. A quick literature search revealed that previous efforts in the synthesis of chiral NHC palladacycles typically involved chiral starting materials like (S)-(-)-(1,1'-Binaphthalene-2,2'-diyl)bis(diphenylphosphine); BINAP and oxazolines, and to the best of our knowledge, none of the abovementioned pyridine-NHC palladacycles exhibited any chirality in the carbon chelate backbone.…”
Section: Introductionmentioning
confidence: 99%